Using N-doped Carbon Dots Prepared Rapidly by Microwave Digestion as Nanoprobes and Nanocatalysts for Fluorescence Determination of Ultratrace Isocarbophos with Label-Free Aptamers - Li, Xin (Nanomaterials (Basel), 2019)
The strongly fluorescent and highly catalytic N-doped carbon dots (CD(N)) were rapidly prepared by a microwave irradiation procedure and were characterized by electron microscopy (EM), laser scattering, infrared spectroscopy (IR), and by their fluorescence spectrum. It was found that the CD(N) had a strong catalytic effect on the fluorescence reaction of 3,3′,5,5′-tetramethylbenzidine hydroxide ((TMB)–H(2)O(2)) which produced the oxidation product of TMB (TMB(OX)) with strong fluorescence at 406 nm. The aptamer (Apt) was adsorbed on the CD(N) surfaces which weakened the fluorescence intensity due to the inhibition of catalytic activity. When the target molecule isocarbophos (IPS) was added, it reacted with the Apt to form a stable conjugate and free CD(N) which restored the catalytic activity to enhance the fluorescence. Using TMB(OX) as a fluorescent probe, a highly sensitive nanocatalytic method for determination of 0.025–1.5 μg/L IPS was established with a detection limit of 0.015 μg/L. Coupling the CD(N) fluorescent probe with the Apt–IPS reaction, a new CD fluorescence method was established for the simple and rapid determination of 0.25–1.5 μg/L IPS with a detection limit of 0.11 μg/L.